Activities of the little cormorant, Phalacrocorax niger (Vieillot) in relation to sunlight in captivity - Naher, Habibin; Sarker, Noor Jahan (Ecoprint: An International Journal of Ecology, 2010)
The study of the activities of the little cormorant was carried out from November 2000 to October 2001 in Dhaka Zoo. Mirpur, Bangladesh. Time spent in preening was the highest (32.25 min/h) in rainy day. Lowest (22.47 min/h) in cloudy day and intermediate (14.73 min/h in sunny day. They eested the highest time (20.77 min/h) in sunny day. Key words: Phalacracorax niger, Sunlight; Captivity doi: 10.3126/eco.v12i0.3200 Ecoprint: An International Journal of Ecology 12: 65-69, 2005